Inblandningsförsök i sulfidjord från provlokaler mellan Umeå och Happaranda : En jämförelse mellan naturlig jords tekniska egenskaper och erhållen skjuvhållfasthet i laboratorium - Burman, Viktor (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2025)
Binder stabilized columns have been used as a ground reinforcement method in Sweden since the 1970s, primarily in road and railway embankments, to increase consolidation, ensure enough stability, and reduce settlements. However, the results of stabilization in sulfide soils or soils with high sulfide content have been variable. Stabilization of sulfide soils has been found to yield less successful outcomes compared to the stabilization of Swedish inorganic clays. The objective of this study is to examine the relationship between the shear strength achievable through laboratory mixing text andthe technical properties of unstabilized soil, along with variations in binder recipes and mixing quantities. The aim is then to develop recommendations for the selection of optimal recipes and mixing quantities, taking into account the natural soil properties, in order to meet the design criteria for softand semi-hard columns. This enables an early assessment of whether the desired shear strength can be achieved in a laboratory environment, and thereby determining the suitability of the method. The study is based on data collected from ten subareas across six different test sites located between Umeå and Haparanda. For each subarea, all available geotechnical parameters were obtained from the depths at which laboratory mixing test were conducted. In cases where multiple values were available for the same mixing depth, an average was calculated, and variations were recorded. The most frequently used recipes in this study were cement 100 (C 100), lime/cement 30/70 (KC 30/70) and lime/cement 50/50 (KC 50/50). The most examined mixing quantities for each recipe were 100– 120 kg/m³, 140–160 kg/m³, and 175–200 kg/m³. As a result, the study has been limited to these specific recipes and mixing quantities. The initial results investigated the relationship between geotechnical parameters in unstabilized soil. Subsequently, all examined geotechnical parameters were analyzed in relation to the shear strength obtained from the mixing ...